Performance comparison of bluetooth beacon and reverse RFID systems as potential tools for measuring truck travel time in open-pit mines: a simulation experiment. Issue 1 (2nd January 2018) - Baek, Jieun; Choi, Yosoon; Lee, Chaeyoung; Jung, Jihoo
Abstract: We compared the performance of a Bluetooth beacon system and a reverse Radio-Frequency Identification (RFID) system to investigate their potentials as tools for measuring truck travel time in open-pit mines. A university campus was chosen as the simulation experiment site, and Bluetooth beacons and RFID tags were installed at intervals along the car's course. A car equipped with a smartphone that can recognize beacons and an RFID reader that can communicate with the tags was driven along the course; the travel time and recognition rate were measured. For comparison of the travel time measurement data, we used video data captured while driving the car. The analysis results of ten rounds of experimental measurement data show that the average time error is 1.14 and 0.80 s for the Bluetooth beacon and reverse RFID systems, respectively. The sensor recognition rate is an average of 98% for the Bluetooth beacon system and 61% for the reverse RFID system. The reverse RFID system is slightly more accurate as a tool for measuring car travel time, and the Bluetooth beacon system has a much better sensor recognition rate.